STUDI KOMPARATIF TENTANG KARAKTER TOLERANSI ANTARA SISWA LAKI-LAKI DENGAN SISWA PEREMPUAN KELAS X DI SMA NEGERI 1 TUALANG - Raie Restu Mentari; Ahmad Eddison; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the fading of students' tolerant attitudes male students and female students. From the symptoms at school, it can be seen that the tolerance of students is quite low in several aspects. Which psychologically men and women differ both physically and psychologically. The formulation of the problem in this study is